SISTEM INFORMASI E-KATALOG PERPUSTAKAAN MUSEUM NEGERI NUSA TENGGARA BARAT BERBASIS WEBSITE - Ulya, Uswatul; Murpratiwi, Santi Ika; Luqyana, Salsabila (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2024)
Library digitalization has become increasingly important in the era of information technology development. Digitalization enables libraries to provide easier and more efficient access to various information sources. This study proposes to design and construct an online e-catalog information system for the Nusa Tenggara Barat State Museum Library, which currently relies on manual book searches. The waterfall model was the software development methodology utilized in this study. This research is designed to facilitate library data management and assist visitors in finding the books they need. The implementation of this system includes features such as sign-in, dashboard, profile, services, and catalog. The testing results demonstrate that the system is intuitive, offers comprehensive information, and all functionalities function as intended. In conclusion, this e-catalog information system successfully improves the effectiveness of library services and simplifies book data management.